The image of the hero of Ukrainian fairy tales in the context of differentiation and transformation of the hierarchy of socio-cultural practices - Pavlova, Olena; Rohozha, Mariya (Ukrainian Cultural Studies, 2024)
Background. The Modern era, with its paradoxes of innovation and repetition, shaped the "discovery of the people" and rekindled interest in folktales. Enlightenment models of fairy tales emphasized the ethical dimension, while the romantic moods of the 19th century stirred European communities' interest in gathering national and regional versions of folktales and converting them into literary fairy tales. The perspective of contemporary humanities proves to be quite productive to enhance the understanding of the cultural potential of Ukrainian fairy tales in bridging diverse traditions and generating images. Methods. The methodological basis for the study is a content analysis of a collection of fairy tales. A categorization is based on the titles of folktales and the classifications of J. Campbell's transformations of the hero. The interpretation of the data is made in optics of the differentiation of a segmentary society and the specifics of its transformations of representation practices, first of all the image and the image of a hero. The aim of the article is to define fundamental characteristics of the image of a hero in Ukrainian fairy tales as a way of representation in logics of the differentiation of a segmentary community. Results. The differentiation of practices begins with the complexification of a segmentary society, where storytelling practices were detached from the original ritual syncretism in the logic of ethnic diversity production and strata hierarchy. Each stratum nurtured its storytelling genre and thematic uniqueness. With its functioning in the magical and practical unity of the peasant stratum, the folktale preserved the most archaic narrative structure, with corresponding images of the main characters and logic of image construction. The image of the folktale hero became the leading practice in representing communities. Conclusions. A content analysis of a collection of Galician folktales reveals the replication of the classic triad of popular culture "Heroes, Villains and Fools" (P. Burke), marked by a dominant quantitative representation of the fool's image. A fairy tale hero is a dormant hero, leaving the impression that everybody can find their place. The hero's heroic powers are exposed gradually, and the hero possesses definite traits and personifies moral integrity. These qualities allow the overcoming of obstacles and passing of tests. Usually, the hero of a Ukrainian fairy tale is a trickster who can maneuver through society. The ethical pathos of a fairy tale consists of a victorious war between evil and justice/resumption. The predominantly happy ending of Ukrainian fairy tales suggests these functions provide a therapeutic effect in difficult historical circumstances.
Keywords: representation of the image of a hero; ritual; initiation; invention of tradition; transformation of socio-cultural practices; the image of a hero; a dormant hero; virtues